2009
DOI: 10.3126/eco.v15i0.1943
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Spotted Flapshell Turtle, <i>Lissemys punctata</i> (Lacepede, 1788) in Bangladesh

Abstract: Spotted flapshell turtle, Lissemys punctata was found in all types of habitats of Bangladesh. Of the 9 categories of habitats studied, the highest number (17.42%) of the turtle species was found in marshland followed by puddles (17.26%), agriculture fields (17.12%), streams (12.1%), canals (10.54%), tanks (10.39%), derelict ponds (9.18%) and domestic ponds (6.08%). Most of the time the turtle was found in burrowing condition (55.83%), rarely it was observed in feeding (7.2%) condition. The turtle seem to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This also elucidates their absence in hilly regions where the stream beds consist mostly of pebbles and rocks that possibly will not serve as good refuge grounds. Hossain et al (2008) reported that marshlands and agricultural fields were the most preferred habitats of L. punctata, followed by ponds, streams, and lakes. On the contrary, M. trijuga preferred streams (30.11%), agricultural lands (26.7%), and ponds (22.16%) followed by wetlands (6.81%), rivers (5.68%), drainages (2.84%), and gardens (1.14%).…”
Section: Discussionmentioning
confidence: 99%
“…This also elucidates their absence in hilly regions where the stream beds consist mostly of pebbles and rocks that possibly will not serve as good refuge grounds. Hossain et al (2008) reported that marshlands and agricultural fields were the most preferred habitats of L. punctata, followed by ponds, streams, and lakes. On the contrary, M. trijuga preferred streams (30.11%), agricultural lands (26.7%), and ponds (22.16%) followed by wetlands (6.81%), rivers (5.68%), drainages (2.84%), and gardens (1.14%).…”
Section: Discussionmentioning
confidence: 99%
“…The Indian Flapshell Turtle (Lissemys punctata) is a softshelled turtle that is widely distributed across the Indian Subcontinent, where it inhabits habitats that include metropolitan, agricultural, and natural aquatic systems (Das 1991;Moll and Moll 2004;Hossain et al 2008;Krishnakumar et al 2009). Lissemys punctata is known to move through terrestrial areas during drought conditions and monsoons due to suboptimal water levels (Bhupathy et al 2014).…”
Section: O N S E R V At I O N a N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…Freshwater turtles in muddy environments, medium-size rivers, dams, and ponds are considered as water purifiers as it contributes to the reduction of algal bloom and are indicators of pollution [4, 23,28,36]. Soft-shell turtles are a useful source of protein [11,17,37] and used for purifying blood and cure respiratory diseases and intestinal disorders [13,24]. Several factors such as habitat fragmentation, pollution, introduction of exotic species, hunting, and global climate change affect the biodiversity of turtle fauna [5,9,19,21,22].…”
Section: Introductionmentioning
confidence: 99%